Utilization of a whole genome SNP panel for efficient genetic mapping in the mouse - Moran, Jennifer L.; Bolton, Andrew D.; Tran, Pamela V.; Brown, Alison; Dwyer, Noelle D.; Manning, Danielle K.; Bjork, Bryan C.; Li, Cheng; Montgomery, Kate; Siepka, Sandra M.; Vitaterna, Martha Hotz; Takahashi, Joseph S.; et al. (Genome Research, 2006)
Phenotype-driven genetics can be used to create mouse models of human disease and birth defects. However, the utility of these mutant models is limited without identification of the causal gene. To facilitate genetic mapping, we developed a fixed single nucleotide polymorphism (SNP) panel of 394 SNPs as an alternative to analyses using simple sequence length polymorphism (SSLP) marker mapping. With the SNP panel, chromosomal locations for 22 monogenic mutants were identified. The average number of affected progeny genotyped for mapped monogenic mutations is nine. Map locations for several mutants have been obtained with as few as four affected progeny. The average size of genetic intervals obtained for these mutants is 43 Mb, with a range of 17–83 Mb. Thus, our SNP panel allows for identification of moderate resolution map position with small numbers of mice in a high-throughput manner. Importantly, the panel is suitable for mapping crosses from many inbred and wild-derived inbred strain combinations. The chromosomal localizations obtained with the SNP panel allow one to quickly distinguish between potentially novel loci or remutations in known genes, and facilitates fine mapping and positional cloning. By using this approach, we identified DNA sequence changes in two ethylnitrosourea-induced mutants.
10.1101/gr.4563306